Determination of Sulphur Contents of Tomato Grown in Greenhouses in West Mediterranean Region, Turkey - Orman, Sule; Kaplan, Mustafa (Asian Journal of Chemistry, 2010)
Sulphur contents of soils and tomato plants grown as single crop in greenhouses in Kumluca and Finike districts in Turkey were determined. For this purpose, 20 tomato greenhouses in each district were used as the source of soil samples from 0-20 and 20-40 cm depths prior to planting (1st sample period) and in the middle of the growing season (2nd sample period). When the soil samples in 2nd period were taken, plant samples were also collected. While the average SO42--S contents of soil samples in the 1st and 2nd periods were determined to have similar values in Kumluca. These values for the 2nd period were higher than the 1st period in Finike in both 0-20 and 20-40 cm depths. Considerable relationships were found between the values of 2nd period soil samples and some other soil properties. Whilst, negative correlations were observed between SO42--S contents of soils and pH and sand contents, positive correlations were observed between EC values, clay contents, N, K and Na contents. Sulphur status of soils and plants were determined to be sufficient contents in both Kumluca and Finike districts. However, a sulphur deficiency is not determined in both district's tomato plants, it appears that there is not a balance nutrition for N:S and S:P rate.